2019
DOI: 10.1109/jstsp.2019.2904212
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control in Remote Speech Data Collection

Abstract: There is the need for algorithms that can automatically control the quality of the remotely collected speech databases by detecting potential outliers which deserve further investigation. In this paper, a simple and effective approach for identification of outliers in a speech database is proposed. Using the deterministic minimum covariance determinant (DetMCD) algorithm to estimate the mean and covariance of the speech data in the mel-frequency cepstral domain, this approach identifies potential outliers base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding academia, it is reported that 78% of UK Higher Education staff wish to continue with hybrid-working (Taylor et al, 2021), higher education managers' attitudes regarding staff homeworking are also significantly more positive now than prepandemic (Forbes et al, 2020). As a result, there is the need to consider practical constraints for remote data collection, as there are several aspects which need to be considered as we rely more on online technology platforms for data collection and there is a growing body of research in this field that have considered the various challenges involved (e.g., Zhang et al, 2021;Poorjam et al, 2019;Gregory et al, 2022). The following section aims to consider some key practical areas which might in turn serve as a framework to evaluate the practical considerations for optimal data collection.…”
Section: Need For Remote Data Collectionmentioning
confidence: 99%
“…Regarding academia, it is reported that 78% of UK Higher Education staff wish to continue with hybrid-working (Taylor et al, 2021), higher education managers' attitudes regarding staff homeworking are also significantly more positive now than prepandemic (Forbes et al, 2020). As a result, there is the need to consider practical constraints for remote data collection, as there are several aspects which need to be considered as we rely more on online technology platforms for data collection and there is a growing body of research in this field that have considered the various challenges involved (e.g., Zhang et al, 2021;Poorjam et al, 2019;Gregory et al, 2022). The following section aims to consider some key practical areas which might in turn serve as a framework to evaluate the practical considerations for optimal data collection.…”
Section: Need For Remote Data Collectionmentioning
confidence: 99%
“…Quality control of the voice recordings is typically performed manually by human experts which is a very costly and time consuming task, and is often infeasible in online applications. In [17], the problem of quality control in remote speech data collection has been approached by identifying the potential outliers which are inconsistent, in terms of the quality and the context, with the majority of speech samples in a data set. Even though very effective in finding outliers, it is not capable of detecting the type of degradation nor identifying short-term protocol violations in recordings.…”
Section: Introductionmentioning
confidence: 99%